Factors Affecting Presbycusis on Audiogram Overview at H. Adam Malik General Hospital Medan - Frenky Sorimuda Manullang; Adlin Adnan; Delfitri Munir (Masters Program in Public Health, 2021)
Background: Presbycusis incidence is thought to have a relationship with hereditary factors, metabolism, atherosclerosis, noise and lifestyle. The presbycusis classification consists of Sensory (outer hair-cell), neural (ganglion-cell), metabolic (strial atrophy), and conductive cochlea (stiffness of the basilar membrane). Factors that influence presbycusis include age, gender, genetics, hypertension, gout, diabetes mellitus, hypercholesterolemia, noise exposure, and smoking. This study aims to determine the factors that influence presbycusis on the audiogram image at H. Adam Malik Hospital Medan. Subjects and Method: This study was an analytical study with a cross sectional design in elderly patients at the polyclinic. The study was conducted in November to December 2019. The dependent variable was the incidence of presbycusis. The independent variables were uric acid levels, blood sugar levels, smoking habits, hypercholesterolemia, and hypertension. Data were analyzed by using chi square test. Results: The prevalence of presbycusis in the 45-59 years age group was 39 people (54.2%) and the 60-74 years age group was 33 people (45.8%). In this study, it shows that male respondents are more than female respondents, where the number of men is 58 people (80.6%) and women are 14 people (19.4%). Based on presbycusis type, there were 33 (45.9%) people (normal), 18 (25%) people (strrial type), 7 (7.9%) people (neural type), 7 (7.9%) people (sensory type), 7 (7.9%) people (cochlear type). High sugar content (OR= 3.33; 95% CI= 1.81 to 6.13; p <0.001), uric acid levels (OR= 2.36; 95% CI= 1.19 to 4.70; p= 0.005), total cholesterol levels (OR= 3.33; 95% CI= 1.81 to 6.13; p <0.001), and smoking (OR= 1.90; 95% CI = 1.21 to 2.97; p= 0.016) increased the risk of presbycusis. Conclusion: High sugar levels, uric acid levels, total cholesterol levels, and smoking habits increase the risk of presbycusis.